2016
DOI: 10.1007/978-3-319-42070-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness Through Time Management

Abstract: As an imperative resource, time and the usage of it should be analyzed and planned in a proper way to maximize the individual effectiveness, and thus make the time management as a functioning tool. Innovativeness is not any easier issue to master, but if a time personality is understood and taken account, a per-son´s innovativeness can be effectively utilized. Innovativeness as a concept must be seen from a wider perspective, including both capability and willingness to act, resulting different kinds of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Research was done by utilizing application called Chronos & Kairos (C&K) (Reunanen 2015;2016), which main purpose is to reveal individuals' conscious awareness towards time and to give possibility for thorough research for peoples' differences when experiencing and managing time. C&K is part of Co-Evolute research tool.…”
Section: Research Initial Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Research was done by utilizing application called Chronos & Kairos (C&K) (Reunanen 2015;2016), which main purpose is to reveal individuals' conscious awareness towards time and to give possibility for thorough research for peoples' differences when experiencing and managing time. C&K is part of Co-Evolute research tool.…”
Section: Research Initial Samplementioning
confidence: 99%
“…Former studies have already found that people posses different time personalities and time's face towards people is situation related (Reunanen 2015a;2015b). There also seems to be correlation and connection between time and innovation management (Reunanen, Windahl & Vanharanta 2016;Reunanen & Vanharanta 2018) and correlations between time management and organizational commitment (Reunanen & Einolander 2020). The purpose of this study is to deepen the understanding human factor in time management and scrutinize the certain feature of procrastination in it.…”
Section: Introductionmentioning
confidence: 99%
“…For the demographic group (sex, age, dedication), the condition of students that are dedicated to work and study plays a significant role. According to the authors Reunanen, Windahl and Vanharanta [10], Hitka et al [11], Kampf et al [12], time should be an indispensable source and its use should be analyzed and planned correctly so that individual effectiveness can be maximized and thusly making time management a functional tool. Aeon and Aguinis [13] think that time management is an important skill that should be acquired by all university students because it is one of the key factors of ensuring excellent achievements in academia.…”
Section: Introductionmentioning
confidence: 99%